ANALISIS PENGARUH BAHASA KEKINIAN PADA IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA TERHADAP SISWA MTS MAMBAUL ULUM - Amri., Sholihul (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2026)
The central research question of this study concerns the influence of contemporary Indonesian on the Indonesian language learning of students at the Mambaul Ulum High School, Lamongan District. The aim of the study is to determine the influence of contemporary Indonesian on the use of standard Indonesian in the school environment of seventh-grade students at the Mambaul Ulum High School, Lamongan, using observation, note-taking, and documentation techniques.This research is qualitative and descriptive. The research methods include data collection, reduction and presentation, review, and drawing conclusions. The subjects were 15 seventh-grade students at the Mambaul Ulum Pucuk High School, Lamongan District. The results indicate that the use of contemporary Indonesian by students, especially at the Mambaul Ulum Pucuk High School, Lamongan District, has become common practice, as it is frequently used in communication and interaction among students, especially among each other.